2022
DOI: 10.1093/cid/ciac378
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of BNT162b2 Messenger RNA Vaccine Induces Airway Immunity in Severe Acute Respiratory Syndrome Coronavirus 2 Naive and Recovered Coronavirus Disease 2019 Subjects

Abstract: Background Mucosal antibodies can prevent virus entry and replication in mucosal epithelial cells and hence virus shedding. Parenteral booster injection of a vaccine against a mucosal pathogen promotes stronger mucosal immune responses following prior mucosal infection compared to injections of a parenteral vaccine in a mucosally naive subject. We investigated whether this was also the case for the BNT162b2 COVID-19 mRNA vaccine. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, analyses of drug concentrations in NLF have been hindered by a lack of convenient, reliable sampling methods (e.g., swabs or nasal lavage) that yield low analyte concentrations which, in turn, produce broad reported ranges for the partition ratio of biopharmaceuticals into the nasopharynx. Common methods for mAb bioanalysis in NLF consist of ELISA, , electrochemiluminescence, , bead-based antibody assays, , and other commercially available serological assays . Generally, the ELISA assays were semiquantitative, , intended for research purposes only (with manufacturer reported range of 250–16,000 pg/mL), or reported standard curve in the ng/mL range (0.195–200 ng/mL) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, analyses of drug concentrations in NLF have been hindered by a lack of convenient, reliable sampling methods (e.g., swabs or nasal lavage) that yield low analyte concentrations which, in turn, produce broad reported ranges for the partition ratio of biopharmaceuticals into the nasopharynx. Common methods for mAb bioanalysis in NLF consist of ELISA, , electrochemiluminescence, , bead-based antibody assays, , and other commercially available serological assays . Generally, the ELISA assays were semiquantitative, , intended for research purposes only (with manufacturer reported range of 250–16,000 pg/mL), or reported standard curve in the ng/mL range (0.195–200 ng/mL) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a highly sensitive LBA-LC-MS/MS-based assay was developed and qualified for the absolute quantification of the two mAbs in human NLF. NLF is a hitherto under-evaluated matrix gaining interest as a patient-centric matrix in studies of COVID-19, ,,, and other respiratory diseases. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were acquired on the V-PLEX® Sector Imager 2400 plate reader and analyzed using Discovery Workbench 3·0 software. NELF antibodies were assessed for their ability to inhibit the binding of a soluble ACE2 to Spike of the ancestral SARS-CoV-2 strain and its Delta and Omicron variants using the multiplex V-PLEX® SARS-CoV-2 Panel 13 ACE2 Kit as described 10 . NELF were diluted 10-fold before being assessed for binding inhibition.…”
mentioning
confidence: 99%
“…Serum albumin concentration in NELF was more than 100-fold lower in NELF compared to serum ruling out the possibility that collecting nasal fluids using swabs could have irritated the epithelia eventually increasing exudation of tissue fluids. IgA and IgG to Spike of the SARS-CoV-2 ancestral strain and of its Delta and Omicron variant were measured using the V-PLEX® SARS-CoV-2 Panel (MSD, Maryland, US), as described 10 . Total IgA and IgG levels were measured using the V-PLEX® Isotyping Panel 1 Human/NHP Kit.…”
mentioning
confidence: 99%